On the use of structural funds - McCarthy, Thomas G. (Statistical and Social Inquiry Society of Ireland, 1993)
Recent efforts to secure EC funding by Irish governments, and in particular Irish officials, have been a resounding success. A priori one might expect that the richest country would be the largest net contributor in GDP share terms and the poorest country the largest net recipient. Our a priori expectation is not fulfilled. However, these are not such as to alter the main message. Ireland does very well from the EC in financial terms. This is no surprise and it serves merely to confirm the perception that we are experts in the art of "grantmanship". But will this success translate itself into a permanent improvement in our welfare? Are there any principles that can guide the spending of this money so as to best achieve this end? These are questions for tonight's symposium. This contribution will consider the impact that public expenditure can have on economic growth. In particular we survey some recent evidence on this issue. We conclude with some tentative lessons which may provide a basis for our discussion.
Symposium on Structural and Cohension Funds
Read before the society, 4 March 1993
Keywords: Structural funds; Productivity; 314.15